Comunidades de aprendizagem: contribuições da perspectiva dialógica para a construção positiva das identidades das crianças negras na escola - Constantino, Francisca de Lima (2010)
The present research, titled Learning Communities: contributions of the dialogic perspective to the positive construction of the black children s identities at school, aimed at understanding which classroom practices contribute to the positive constitution of the black children and the respect for the differences under the dialogic perspective, as well as which practices need to be overcome according to the teacher s point of view in the investigated classroom, the children s and their relatives . In this sense, the objectives were as follows: systematize the identity and diversity concepts under the dialogic perspective; investigate which tools the teacher used to deal with the diversity matter, as well as understanding how the ethnic and racial diversity are perceived by the teacher, children and relatives; and understand, based on the accounts given by the teachers and the school coordinators, how the Learning Communities proposal and its theoretical basis contribute to the positive construction of the identities. In order to fulfill such objectives, we focused on the theoretical bases which rule the Learning Communities proposal and which approach is guided by Habermas communicative action and Freire s dialogicity, as well as having the dialogic learning developed by Flecha as its guiding principle. In addition to these authors, we were also based on other sociology and anthropology theorists who helped us to understand the question of ethnic and racial relations. Furthermore, we were also based on authors from the Special Center of Investigation in Theories and Practices to Overcome Inequality (CREA) and Nucleus of Investigation and Social and Educational Action (NIASE), once such research groups carry out works based on the dialogic perspective. Learning Communities is a proposal which was born from the experiences that Spain and The United States went through and it is currently being developed in Latin American countries such as Brazil first of all, followed by Chile and recently Paraguay. The Learning Communities proposal aims at the social and cultural transformation of the school and its surroundings based on the principles of the dialogic learning and seeks maximum-quality education for everyone. The dialogic learning principles guide us through coming up with more equal ethnic and racial relations within the school context, thus aiming at the construction of the different identities. The research was carried out at a school which was made into a Learning Community in the city of São Carlos. The teacher responsible for a 3rd-year group and his/her pupils, as well as the pedagogical coordinators of the school and some relatives took part in the investigation. Based on the critical communicative methodology, the data collection was carried out from the communicative accounts, discussion groups and communicative observations; the analyses took place intersubjectively between the participants and the researcher. As for the results, it can be affirmed that the dialogic perspective turns into a possibility in seeking the transformation of the school relations and that it is possible to form and value the different identities in the school context. Through the speeches of the participants, it can be affirmed that the Learning Communities theoretical bases contribute to the positive constitution of the black identity and that the dialogue is an action which effects more equal relations in the classroom. Moreover, it can be noted that the diversity contributes to both the children s learning and to the strengthening of their identities. In conclusion, ethnic and racial relations is a complex matter as we could observe, and it is not yet resolved in the political, social and educational scopes of our country. Therefore, questions to be answered in future studies remain.